Expression of two barley proteinase inhibitors in tomato promotes endogenous defensive response and enhances resistance to Tuta absoluta - Rim Hamza; Meritxell Pérez-Hedo; Alberto Urbaneja; José L. Rambla; Antonio Granell; Kamel Gaddour; José P. Beltrán; Luis A. Cañas (BMC Plant Biology, 2018)
Abstract Background Plants and insects have coexisted for million years and evolved a set of interactions which affect both organisms at different levels. Plants have developed various morphological and biochemical adaptations to cope with herbivores attacks. However, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) has become the major pest threatening tomato crops worldwide and without the appropriated management it can cause production losses between 80 to 100%. Results The aim of this study was to investigate the in vivo effect of a serine proteinase inhibitor (BTI-CMe) and a cysteine proteinase inhibitor (Hv-CPI2) from barley on this insect and to examine the effect their expression has on tomato defensive responses. We found that larvae fed on tomato transgenic plants co-expressing both proteinase inhibitors showed a notable reduction in weight. Moreover, only 56% of these larvae reached the adult stage. The emerged adults showed wings deformities and reduced fertility. We also investigated the effect of proteinase inhibitors ingestion on the insect digestive enzymes. Our results showed a decrease in larval trypsin activity. Transgenes expression had no harmful effect on Nesidiocoris tenuis (Reuter) (Heteroptera: Miridae), a predator of Tuta absoluta, despite transgenic tomato plants attracted the mirid. We also found that barley cystatin expression promoted plant defense by inducing the expression of the tomato endogenous wound inducible Proteinase inhibitor 2 (Pin2) gene, increasing the production of glandular trichomes and altering the emission of volatile organic compounds. Conclusion Our results demonstrate the usefulness of the co-expression of different proteinase inhibitors for the enhancement of plant resistance to Tuta absoluta.